2019
DOI: 10.1182/blood-2019-129751
|View full text |Cite
|
Sign up to set email alerts
|

Phase 1 Trial of K0706, a Novel Oral BCR-ABL1 Tyrosine Kinase Inhibitor (TKI): In Patients with Chronic Myelogenous Leukemia (CML) and Phildelphia Positive Acute Lymphoblastic Leukemia (Ph+ ALL) Failing ≥ 3 Prior TKI Therapies: Initial Safety and Efficacy

Abstract: Introduction: Despite availability of several BCR-ABL1 TKIs for treatment of CML, some patients (pts) fail ≥3 TKIs and/or have co-morbidities that limit use of 2nd generation TKIs (2GTKI: Nilotinib, Dasatinib and Ponatinib). K0706 is a novel third generation TKI effective against wild-type and mutated BCR-ABL1 isoforms with significantly less off-target activity compared to existing TKIs. We report Phase I results of K0706 in pts who were resistant and/or intolerant to ≥3 prior TKIs or who had co-morbidities p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 0 publications
0
9
0
1
Order By: Relevance
“…Vodobatinib (K0706) is another orally bioavailable BCR-ABL1 TKI designed using a structure-guided drug-design platform with significant activity in vitro against most BCR-ABL mutations, but not T315I [ 73 ]. Vodobatinib showed an acceptable safety profile in a phase I study in patients with CML who experienced treatment failure with ≥ 3 TKIs and/or patients with comorbidities that restrict the use of certain TKIs (nilotinib, dasatinib, and ponatinib) [ 74 , 75 ]. At the time of data cutoff, 35 patients received doses ranging from 12 to 240 mg—27 of whom had CML-CP.…”
Section: Overview Of New Bcr-abl1–targeted Therapies In Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Vodobatinib (K0706) is another orally bioavailable BCR-ABL1 TKI designed using a structure-guided drug-design platform with significant activity in vitro against most BCR-ABL mutations, but not T315I [ 73 ]. Vodobatinib showed an acceptable safety profile in a phase I study in patients with CML who experienced treatment failure with ≥ 3 TKIs and/or patients with comorbidities that restrict the use of certain TKIs (nilotinib, dasatinib, and ponatinib) [ 74 , 75 ]. At the time of data cutoff, 35 patients received doses ranging from 12 to 240 mg—27 of whom had CML-CP.…”
Section: Overview Of New Bcr-abl1–targeted Therapies In Developmentmentioning
confidence: 99%
“…Mild to moderate gastrointestinal AEs were reported in 18.5% of patients. Two patients enrolled had T315I mutations; these patients experienced disease progression in cycle 1 of treatment, leading to a protocol amendment to exclude patients with T315I mutations from this study [ 74 ]. In a recently published exploratory analysis, efficacy, and safety of vodobatinib was assessed in ponatinib-pretreated and -naive patients with CML-CP, with the goal of determining MTD or RP2D.…”
Section: Overview Of New Bcr-abl1–targeted Therapies In Developmentmentioning
confidence: 99%
“…Other AEs included dyspnea and non-cardiac chest pain, both of which returned to normal following dose-reduction. 93 In a 14-day placebo-controlled trial in 46 PD patients, Vodobatinib was reported to be well-tolerated with no serious clinical or laboratory AEs that were considered to be drug-related. Plasma concentrations are reported to have reached levels that were efficacious in PD animal models and CSF measures.…”
Section: Inhibition Of C-abl As a Potential Disease-modifying Therapy For Pdmentioning
confidence: 99%
“…A phase I/II study (NCT02629692) is ongoing to evaluate the efficacy and safety of K0706 in patients with comorbidities precluding the use of conventional secondgeneration TKIs or after ≥ 3 TKIs failure. The initial phase I results of this study showed disease progression in patients carrying BCR-ABL T315I mutation, therefore the enrolment of patients with this mutation was stopped (67).…”
Section: Vodobatinib and Pf-114mentioning
confidence: 99%